Higher fasting blood glucose was associated with worse in‐hospital clinical outcomes in patients with primary intracerebral hemorrhage: From a large‐scale nationwide longitudinal registry. (24th September 2022) - Li, Guangshuo; Wang, Shang; Xiong, Yunyun; Gu, Hongqiu; Jiang, Yingyu; Yang, Xin; Wang, Chunjuan; Wang, Chuanying; Li, Zixiao; Zhao, Xingquan
Abstract: Introduction: Studies that investigated the relationship between fasting blood glucose (FBG) and intracerebral hemorrhage (ICH) outcomes were insufficient. Aim: We aimed to investigate the association between FBG level and in‐hospital clinical outcomes in patients with primary ICH. Results: A total of 34, 507 patients were enrolled in the final study. Compared with the reference group, the ≥6.1 and <7 mmol/L group showed nonsignificant higher in‐hospital mortality (adjusted odds ratio [OR] 1.20, 95% confidence interval [CI] 0.69–2.11, p = 0.52), and a significant higher proportion of intracranial hematoma evacuation (adjusted OR 1.56, 95% CI 1.26–1.92, p < 0.001). The ≥7 mmol/L group showed both significant higher in‐hospital mortality (adjusted OR 2.08, 95% CI 1.42–3.04, p = 0.52) and a significant higher proportion of intracranial hematoma evacuation (adjusted OR 2.09, 95% CI 1.78–2.47, p < 0.001). Conclusion: Higher FBG level was correlated with both higher mortality and proportion of evacuation of intracranial hematoma. Abstract : Studies that investigated the relationship between fasting blood glucose (FBG) and intracerebral hemorrhage (ICH) outcomes were insufficient. We aimed to investigate the association between FBG level and in‐hospital clinical outcomes in patients with primary ICH. Higher FBG level was correlated with both higher mortality and proportion of evacuation of intracranial hematoma.